Peculiarities of traction forces in wheel/rail contact area - Bureika, Gintautas; Mikaliūnas, Šarūnas (Transport, 2002)
Tractive force and train movement stability dependence on division of forces involved in wheel/rail contact area are the main subjects of this article. The influence of wheel/rail contact properties in the vehicle dynamics and adhesion fields is investigated. Current tendency all over the world is to reduce the conicity of wheels with the aim of increasing the speed of trains. Wave-length of moving wheel-set in track for worn wheel-set tyre is twice less than for new wheel running profile.First Published Online: 19 Oct 2011